TINGKAT BERPIKIR KREATIF SISWA MTs. PADA BANGUN DATAR DITINJAU DARI JENIS KELAMIN - Nurmitasari, Nurmitasari; Astuti, Robia (JURNAL e-DuMath, 2017)
Abstract: This study aims to describe: (1) the level of creative thinking of MTs. on a flat wakeÂ student gender male, (2) the level of creative thinking of MTs. on a flat wakeÂ student gender female. The type of research used in this study is descriptive qualitative research, where the subjects were taken using purposive sampling technique. The subjek of this study were 6 students with details of 3 male students and 3 female students. This study uses data analisys technique triangulation of sources that is by reducing data, presenting data, and draw conclusions. The result of this study are: (1) the level of creative thinking of MTs students on the wake of flat student gender male is at level one (less creative); and (2) the level of creative thinking of MTs students on the wake of flat student gender female is at zero level (not creative).Keywords : Level of creative thinking, Gender, Flat Wake